Elevated plasma migration inhibitory factor in hypertension–hyperlipidemia patients correlates with impaired endothelial function. Issue 43 (October 2016) - Zhou, Boda; Ren, Chuan; Zu, Lingyun; Zheng, Lemin; Guo, Lijun; Gao, Wei
Abstract : Abstract: Migration inhibitory factor (MIF) has been shown to be critical in the pathology of early artherosclerosis; this article aim to investigate the plasma levels of MIF in hypertension plus hyperlipidemia patients. A total of 39 hypertension plus hyperlipidemia patients without any previous treatment were enrolled (HTN-HLP). Twenty-five healthy subjects were enrolled as the healthy control group (HEALTHY). Plasma MIF was measured by ELISA; laboratory and clinical characteristics were analyzed. HUVECs were treated with pooled plasma from HTN-HLP and HEALTHY groups, and the protein levels of adhesion molecules VCAM-1 and ICAM-1 were determined by ELISA. We found that plasma MIF was significantly elevated in the HTN-HLP group. Serum NO and eNOS levels were significantly lower; serum ET-1 (endothelin) levels were significantly higher in the HTN-HLP group. Furthermore, blood pressure, baPWV (brachial–ankle pulse wave velocity), and serum ET-1 level were significantly positively; serum NO and eNOS levels were negatively correlated with plasma MIF levels. Plasma from HTN-HLP significantly stimulated VCAM-1 and ICAM-1 protein expression on the surface of HUVECs. Plasma MIF was elevated in HTN-HLP patients and correlates with impaired endothelial function.